Pendekatan Humanistik Dalam Bimbingan Konseling Untuk Meningkatkan Percaya Diri Siswa - Rehanaisha, Rehanaisha (Jurnal Ilmu Bimbingan dan Konseling, 2024)
Self-confidence is an essential aspect of student development, influencing both academic and social success. However, many students face challenges that hinder the growth of their self-confidence, such as academic pressure and interpersonal issues. The humanistic approach in counseling offers a solution by emphasizing a holistic understanding of individuals, empathy, and unconditional positive regard. This article explores the principles of the humanistic approach based on Carl Rogers' theory, as well as its implementation in helping students improve their self-confidence. The findings indicate that this approach is effective in creating a supportive counseling environment, enabling students to recognize their potential, overcome low self-esteem, and develop optimally.